“Urip Mung Mampir Ngguyu” :Tinjauan Falsafah Jawa dan Akhlak Humor - Robingun Suyud El Syam; Salis Irvan Fuadi; Ngatoillah Linnaja (Departement of Mathematics Education, 2023)
Human nature tends to happiness and pleasure which is the driving force for the expression of laughter. The Al-Qur'an and Hadith discuss it a lot, medical facts also find a variety of benefits. It's a pity, laughing harms others. With a theoretical study, he concluded: